PHYSICAL EXCLUSION OF UNLAWFULLY OBTAINED EVIDENCE - Mircea-Constantin SINESCU; Alin-Sorin NICOLESCU (Challenges of the Knowledge Society, 2024)
The aim of this study is to highlight some of the latest tendencies in the criminal court decisions ruled in the stage of the preliminary chamber regarding the exclusion of unlawfully obtained evidence, in light of the CCR decisions issued in the last years. The exclusion of unlawfully obtained evidence from criminal proceedings as a legal consequence of annulment of the tainted evidence is merely an elimination of the possibility of the judge to rely on such evidence in the solving of the case, but it does not erase from the magistrate's memory the information he or she has become aware of from the tainted evidence, this being the main argument for the positive trend of judicial practice in this specific area. Consequently, the recent court decisions are a strong emphasis of the CCR arguments that conclude that exclusion by law of evidence that was obtained unlawfully in criminal proceedings, in the absence of physical removal of such evidence from the criminal case file is not enough to actually guarantee compliance with the rule of presumption of innocence and the right to a fair trial. Although the CCR decision seems to be quite explicit, difficulties have arisen in judicial practice regarding application of the aforementioned provisions, therefore the recent court decisions highlight the necessity of complete physical exclusion of any mentioning or reference regarding the unlawfully obtained evidence.